ESTIMATION AND IMPROVEMENT OF THE RF GOVERNMENT PLAN FOR PROVIDING THE SUSTAINABLE SOCIAL-ECONOMIC DEVELOPMENT OF RUSSIA IN 2016 - D. V. Manushin (Russian Journal of Economics and Law)
Objective: to assess the anti-crisis plan of the RF Government of January 27, 2015, to project them onto the anti-crisis plan of the RF Government dated March 1, 2016, to identify its problems and suggest measures for their solution.Methods: abstract-logical.Results: the modern Russian economy is facing severe challenges posed by the crisis in the economy, Western sanctions and foreign policy of the country. The government, aware of these problems, for the second year in a row adopts and implements a program of anti-crisis measures. Analysis of scientific literature, reports of the government and supervisory bodies allowed to formulate conclusions on the low efficiency of the anti-crisis plan of 27 January 2015. Most of the indicators have not been achieved, in many areas the objectives and their implementation have been haphazard, with immeasurable results and lack of accountability for results.Манушин Д. В. Оценка антикризисных планов Правительства РФ в 2015 и 2016 годах и совершенствование плана Правительства РФ ... Manushin D. V. Estimation and improvement of the RF Government plan for providing the stable social-economic development of Russia in 201624Экономика и управление народным хозяйствомEconomics and economic managementАктуальные проблемы экономики и права. 2016. Т. 10, № 3Actual Problems of Economics and Law, 2016, vol. 10, No. 3 ISSN 1993-047Х (Print) / ISSN 2410-0390 (Online) Analysis of the structure of anti-crisis measures of the Russian government for 2016 demonstrated the persistence of old problems and the emer- gence of new ones. The number of indicators increased, while simultaneously funding reduced, as well as the number of specialists engaged in substantive anti-crisis measures. Inefficient structure of the anti-crisis measures is identified, where priority is given to inappropriate support of the regions and the domestic auto industry to the detriment of the social component, as well as other problems.As a result, the measures are proposed to address the identified problems in the anti-crisis plans of the Russian Government dated 27.01.2015 and 01.03.2016.Scientific novelty: the following basic steps are formulated to address the identified challenges: to modernize the work of the crisis staff; to specify the anti-crisis measures, developing a detailed mechanism for their implementation and indicators for assessing the effectiveness; to increase the motivation of civil servants; to increase the minimum wage to the subsistence minimum; to grant interest-free loans for initial setting of personal farms for the citizens who have received free land from the state; to intensify the work in the field of infrastructure projects implementation; to solve organizational problems of state management of society and the economy, etc.Practical significance: implementation of the proposed measures will improve the crisis management in the Russian macroeconomics.